Penyuluhan Kesehatan Tentang Pencegahan HIV dan AIDS - Sutanta, Sutanta; Hasbi, Habid Al; Rismawati, Rismawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Big changes in the relationships of today's teenagers are caused by the ease of communicating via social media which is growing very rapidly. Delinquency can also cause problems in the family, community and work environment, if children are involved in delinquency it will have an impact on the child's educational and academic achievements. The low level of education in the family causes teenagers to be easily influenced by promiscuity. The most important level of education there is religious education. Parents who do not supervise closely cause teenagers to fall into traps without knowing whether it is true or not.The impact of promiscuity is freedom from free sex and HIV-AIDS. HIV is a very dangerous disease, because this disease is very dangerous for our health. especially for the nation's next generation.Apart from promiscuous sex during adolescence, HIV-AIDS can be self-destructive and have an impact on the structure of family life, the community environment and the school environment, and even directly or indirectly pose a threat to the continuity of development and the future of our beloved nation and state. Teenagers and children who are students need education about the dangers of free sex and drug use, remembering that basically teenagers have a high sense of curiosity and always want to try new things that can be obtained from this information and if this is not accompanied by supervision, guidance and direction from various parties. This community service will be carried out on , Thursday June 15 2023, 09.00 – 11.00 WIB at the MTS Negeri Semarang Mosque. This activity was attended by 70 participants, namely class 8. The activity was coordinated by the service team leader assisted by the school principal and office staff. The activities in this community service take the form of education about the dangers of promiscuity and free sex. After being given counseling about the dangers of promiscuity and free sex, the 32 students present were able to answer questions about the dangers of promiscuity and free sex.